DEPICTION OF POST COLONIALISM IN SOUTH ASIAN CINEMA: A SEMIOTICAL ANALYSIS OF BOLLYWOOD’S FILM PINJAR - Hamza, Hassan; Teo, Miaw Lee (UNIMAS Publisher, 2020)
The concept of Post -colonialism has been broadly used, not only in South Asian society but around the globe to study the relationship between the colonizer and the colonized ones. Like many European and African countries, British ruled the Indian Sub-continent for centuries. The filmPinjaris based on a novel. It portrays the diversity ofcultures, creeds, religions and traditions reflecting the era before and during the partition of Indian sub-continent. It enlightens many literary aspects and critical angles. This study revolves around this film, focusing on post-colonialism especially the partition era of 1947. Pierce’s Model of Semiotics, as a major framework has been adopted to draw all post-colonial aspects from the film Pinjar.